A Cultural Approach To The Study Of Inclusive Education - Ашиток, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. In recent years, the problems of studying the value of inclusive education have become relevant in national education and society. The article examines the influence of cultural values on the development of inclusive education in Ukraine, on the definition of its goals and content and the leading role of its humanistic component in the spiritual, moral and intellectual formation of students on the basis of assimilation of their socio-cultural values. The aim of the article is to study the inculturation of people with special educational needs in the context of the development of national special education. The tasks of the article are to consider the education peculiarities of the children with special educational needs in the institutions of inclusive education in the cultural aspect, to explore the importance of the socio-cultural environment for their development. Research methods. The paper uses general scientific and special research methods. The main among them was the method of analysis. In addition, induction, deduction, etc. were used. Research results. The necessity of introducing culturogical perspective while setting goals for the inclusive education and evaluation of its capabilities is addressed in the article. In the process of education of the people with disabilities it is important to take into account their specific cultural needs. Recognition of the special cultural needs imply the description of the particular system of relationships, the identification systems, the specificity of the constituent elements of cultural environment adequate for people with disabilities, emphasizing the importance of a group as a condition of human development, searching for the language of communication, both for internal needs of this group and for communication with other groups. The need to revise the conceptions of culture in contemporary theory and practice of inclusion is justified towards a more productive use of cultural knowledge in the process of creating a developmental learning environment. The possibility application of cultural forms which can be found in the arsenal of traditional cultures and artistic practices of contemporary art are discussed in creating supportive social and cultural environment that promotes inclusion of people with disabilities into society. Discussion. The views on the content of the inclusive education concept are analyzed. The author substantiates the expediency to denote this term of education for all children who study in a general educational institution. Conclusion. The introduction of elements of social and cultural activities into the inclusive educational process will help the actors of inclusive process master cultural standards and patterns of behavior, meet the spiritual needs and needs for communication, will contribute to their positive perceptions of each other and change the attitude towards the phenomenon of disability. The creative social and cultural environment of the inclusive educational space makes it possible to facilitate the socialization of children with special educational needs.